Powered by Honda : - Nelson, Dave (Wiley, 1998)
Managers learn all about the revolutionary techniques behind Honda of America's record success and how to apply them to their own companies. In Powered by Honda managers, for the first time, get the full story behind Honda America's meteoric rise from a struggling Japanese transplant to an American automotive giant. The authors detail the evolution of Honda's supply-based excellence program which, among other things, entails developing great suppliers rather than merely leveraging existing ones